2016
DOI: 10.1051/sicotj/2016029
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle replacement through a lateral approach: surgical tips

Abstract: Purpose: Recently, the Zimmer Trabecular Metal Total Ankle Replacement (Zimmer TM TAR) was developed to be used through a lateral transfibular approach. The purpose of this paper is to describe the surgical technique and early outcomes of the TAR via the lateral approach using the Zimmer TM TARs. Methods: Sixty-seven patients underwent primary TAR using the Zimmer TM TAR between May 2013 and May 2015. Patients were clinically evaluated preoperatively and postoperatively at six and twelve months and annually us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
1
16
0
2
Order By: Relevance
“…In conclusion, in consideration of the early results of this prosthesis reported in previous studies 16,17 , and of the functional and postoperative pain scores reported in this article, the treatment of ankle osteoarthritis with TAR via lateral transfibular approach can provide reliable pain relief and improvements in range of motion and functional outcomes.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…In conclusion, in consideration of the early results of this prosthesis reported in previous studies 16,17 , and of the functional and postoperative pain scores reported in this article, the treatment of ankle osteoarthritis with TAR via lateral transfibular approach can provide reliable pain relief and improvements in range of motion and functional outcomes.…”
mentioning
confidence: 59%
“…Recently, a novel TAR implant was designed to be performed via the lateral transfibular approach that results in an ideal visualization of the center of rotation and curved resections that allow for sparing bone cuts 16 ; moreover, this approach permits the implantation of components perpendicular to the bone trabeculae, thus limiting the shear forces at the level of the bone-implant interface 16 . This prosthesis consists of a fixed-bearing implant; an alignment coordinate system guides the bone resections and facilitates addressing both coronal and sagittal deformities 17 . The early results of ankle arthroplasty using this TAR implant have been published 12,16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zbog lošijih rezultata, kao i posljedica do kojih dovodi ukočenje gležnja na okolne zglobove 17,18 , danas se kod sve većeg broja pacijenata odlučujemo na ugradnju TEP-a gležnja 10,11 . Razlog je tome i u proizvodnji novih, kvalitetnijih modela endoproteza, kao i u razvoju jednostavnijih kirurških tehnika ugradnje TEP-a gležnja 19 . Rezultati funkcije gležnja nakon ugradnje TEP-a mogu se ispitati različitim standardiziranim ispitnim metodama čija je svrha da se dobiveni rezultati mogu kvalitetno vrednovati i uspoređivati.…”
Section: Raspravaunclassified